HYPERTHYROIDISM IN ADOLESCENT WITH TYPE 1 DIABETES MELLITUS - Luthfi Suhaimi; Eka Agustia Rini (Universitas Fort De Kock, 2020)
hyroid disorders and diabetes mellitus are the two most common endocrine cases in clinical practice. Autoimmune thyroid disease (AITD) being more prevalent in people with type 1 diabetes mellitus (T1DM), and the occurrence of both in the same patient is defined as autoimmune polyglandular syndrome type 3 variant (APS3v). We are presenting a 12-years-old girl with hyperthyroid and T1DM occured as diabetic ketoacidosis (DKA). Diagnosed by symptoms, physical examinations, and confirmed by laboratory results. Patient was treated with insulin injection and oral anti-thyroid drug, and had clinical improvement.